2022
DOI: 10.3390/polym14173609
|View full text |Cite
|
Sign up to set email alerts
|

Loading and Release of Phenolic Compounds Present in Mexican Oregano (Lippia graveolens) in Different Chitosan Bio-Polymeric Cationic Matrixes

Abstract: Mexican oregano (Lippia graveolens) polyphenols have antioxidant and anti-inflammatory potential, but low bioaccessibility. Therefore, in the present work the micro/nano-encapsulation of these compounds in two different matrixes of chitosan (CS) and chitosan-b-poly(PEGMA2000) (CS-b-PPEGMA) is described and assessed. The particle sizes of matrixes of CS (~955 nm) and CS-b-PPEGMA (~190 nm) increased by 10% and 50%, respectively, when the phenolic compounds were encapsulated, yielding loading efficiencies (LE) be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…In other work, when compared to chitosan, copolymers based on chitosan and polyethylene glycol methyl methacrylate (PEGMA) loaded with phenolic compounds (extracted from oregano) resulted in lower particle size (458 nm), more controlled release patterns in response to pH changes, and higher protection for the active agents in simulated gastric conditions (see the cumulative release profiles in Figure 3 ). However, this study revealed that the carrier system prepared with non-modified chitosan (particle size = 1106 nm) had better loading efficiency and was more stable (zeta potential = 50 mV) than the block copolymers-based system (zeta potential = −15 mV) [ 55 ]. In the same way, the encapsulation of quercetin in platforms developed from chitosan and soybean polysaccharides has resulted in nanoparticles with appropriate size (close to 24 nm) for targeting specific cells in the treatment of numerous diseases; in this case, chitosan helped to obtain a more stable complex [ 56 ].…”
Section: Biomedical Application Of Chitosan: Encapsulation Of Active ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In other work, when compared to chitosan, copolymers based on chitosan and polyethylene glycol methyl methacrylate (PEGMA) loaded with phenolic compounds (extracted from oregano) resulted in lower particle size (458 nm), more controlled release patterns in response to pH changes, and higher protection for the active agents in simulated gastric conditions (see the cumulative release profiles in Figure 3 ). However, this study revealed that the carrier system prepared with non-modified chitosan (particle size = 1106 nm) had better loading efficiency and was more stable (zeta potential = 50 mV) than the block copolymers-based system (zeta potential = −15 mV) [ 55 ]. In the same way, the encapsulation of quercetin in platforms developed from chitosan and soybean polysaccharides has resulted in nanoparticles with appropriate size (close to 24 nm) for targeting specific cells in the treatment of numerous diseases; in this case, chitosan helped to obtain a more stable complex [ 56 ].…”
Section: Biomedical Application Of Chitosan: Encapsulation Of Active ...mentioning
confidence: 99%
“…The trials were performed in simulated salivary fluids. The figure was taken from the literature [ 55 ].…”
Section: Figurementioning
confidence: 99%
“…Four flavonoids are flavonols: quercetin, quercitrin, rutin, and kaempferol; two dihydrochalcones identified as phloretin and phloridzin; and one isoflavone identified as genistein (Table 2). The presence of flavonoids in oregano, mostly flavones and flavanones such as apigenin, luteolin-7-glucoside, and naringenin, has been previously reported [21][22][23]. The quantification of flavonoids was carried out based on commercial standards.…”
Section: Identification and Quantification Of Oregano (Lippia Graveol...mentioning
confidence: 99%